2008
DOI: 10.1142/s1793292008001192
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH RATE MEASUREMENT OF C60 FULLERENE NANOWHISKERS

Abstract: The growth rate of C 60 fullerene nanowhiskers ( C 60NWs) prepared by the liquid–liquid interfacial precipitation method is measured and the growth mechanism is discussed. The growth of C 60NWs is investigated from the data obtained at the growth temperatures of 5, 10, 15 and 20°C. It is found that the convection of the solution scarcely influences the growth rate, suggesting that a surface reaction of C 60 molecules dominates the growth process. The activation energy of C 60NWs' growth is estimated at about 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…8(a) and (b) as a function of 1/T, where T is the absolute temperature (K). The length growth rates were calculated from the length increment of the initial 5 min as previously reported [15].…”
Section: For Cases Of Both H 2 O and D 2 O Additionsmentioning
confidence: 99%
See 2 more Smart Citations
“…8(a) and (b) as a function of 1/T, where T is the absolute temperature (K). The length growth rates were calculated from the length increment of the initial 5 min as previously reported [15].…”
Section: For Cases Of Both H 2 O and D 2 O Additionsmentioning
confidence: 99%
“…Not only long fibrous C 60 NWs with lengths greater than several millimeters [13] but also short C 60 NWs with lengths from several micrometers to several tens of micrometers can be prepared by the LLIP method [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5) The growth of [C 60 ]fullerene nanowhiskers is affected by light, temperature, and concentration of water ratio of the poor solvent to the good solvent for [C 60 ]fullerene during the LLIP method. [5][6][7][8][9][10] The polymerization of [C 60 ]fullerene molecules by weak van der Waals interactions has attracted attention due to its promising properties as a carbon nanomaterial. 11,12) [C 60 ]fullerene nanowhiskers polymerize under laser-beam irradiation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the factors of light, temperature, growth time, water and the kind and composition of solvents influence the growth of C 60 NWs when the LLIP method was applied to the synthesis of C 60 NWs [18,19,20].…”
Section: Introductionmentioning
confidence: 99%